PENGARUH MODEL PEMBELAJARAN KOOPERATIF CIRC, JIGSAW, DAN STAD TERHADAP KETERAMPILAN MEMBACA DITINJAU DARI KEMAMPUAN LOGIKA BERBAHASA Studi Eksperimen di Sekolah Dasar Dinas Pendidikan dan Kebudayaan Provinsi Jawa Tengah - ., Murtono (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this research is to investigate: (1) the differences of reading skill between the students who join in CIRC cooperative learning model, Jigsaw cooperative learning model, and STAD cooperative learning model; (2) the differences of reading skill between students who have high and low language logic ability; (3) the influences of the use of the three cooperative learning models and the language logic ability on reading skill. This is an experiment study with 3x2 factorial designs. Manipulation is done towards the learning model variables. The experiment group is provided with a learning treatment involving CIRC, Jigsaw, and STAD learning model. The group is divided into two categories, students who have high language logic ability and those who have low language logic ability. The population of the study is the fifth grade elementary school student in Central Java of 2011/2012 Academic Year. Whereas, the samples are the fifth grade elementary students of 12 Elementary Schools in four regencies/cities, in total involve 364 students taken by multi stage area random sampling technique. The data of reading skill is elicited by reading comprehenson test, while the assessment on the level of language logic ability is done by using test of language logic ability. The data is analized by two-way variant. The results show that: (a) the reading skill of the students who joined in CIRC learning model is better than those who joined in Jigsaw or STAD model, meanwhile the students who joined in Jigsaw and STAD learning model have the same skill level; (b) The reading skill of the students who have high language logic ability is better than those who have low language logic ability; (c) cooperative learning model and language logic ability influence readingskill.